(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article investigates the connection between organized crime and environmental destruction, highlighting how criminal organizations exploit illicit markets for natural resources on a global scale. Through the analysis of case studies from Italy to Latin America, the paper examines the illegal trafficking of hazardous waste, deforestation, and uncontrolled mining activities. Additionally, it emphasizes the growing criminalization of environmental activists, and the impunity enjoyed by those responsible for environmental devastation. The article underscores the need for a collective and ideal space for effective action in addressing environmental protection challenges and combating organized crime.